Peningkatan Kedisiplinan dan Hasil Belajar Operasi Hitung Bilangan Desimal Menggunakan Model PjBL pada Kelas IVA SDK Sorowajan - Tarigan, Oni Alaska Monika Br; Brataningrum, Natalina Premastuti; Rustamti, Maria Indarti (Paedagogie, 2024)
The research is based on low attitude discipline and learning outcomes in mathematics, especially the material for calculating decimal numbers in class IVA SDK Sorowajan in the 2022/2023 academic year. In the initial observation, the results of the disciplinary attitude of students showed an average score of 60 with a percentage of 60% and the learning outcomes of students showed an average score of 59 with a percentage of students who reached KKTP of only 17.39%. The purpose of this study was to (1) describe efforts to improve the disciplinary attitude and learning outcomes of decimal arithmetic operations of class IVA SDK Sorowajan students using the Project Based Learning model. (2) improve the learning outcomes of decimal arithmetic operations of students in class IVA SDK Sorowajan using the Project Based Learning model. This research method is a Classroom Action Research (PTK) model of Kemmis and Mc Taggart with four research stages, namely Planning, Implementation, Observation, and Reflection. The subject of this research was class IVA with a total of 23 students consisting of 14 boys and 9 girls. Data collection techniques were obtained from the results of questionnaires and tests. The results of the disciplinary attitude questionnaire showed an increase in cycle I to 80.65 with a percentage of achievement of 73.91%, and in cycle II it increased to 83.26 with a percentage of achievement of 82.60%. The test results showed an increase in learning outcomes in cycle I to 71.01 with a percentage of achievement of 65.21%, and in cycle II increased to 74.34 with a percentage of achievement of 82.60%. This shows that the learning process of calculating decimal numbers with the Project Based Learning model can improve the attitude of discipline and learning outcomes.